Q: How do you simplify 7a plus 3b minus 4a minus 5b in trig?

Write your answer...

Submit

Related questions

6+7a+6b

11a+7b-(3b-2a)

-6(a-3b-9c)

It is: 4b+6

2a

3A + 9B = 3(A + 3B)

0.6b + 3c

It is: b+4 when simplified

3b2 - 3b = 3b(b - 1)

5b + 11 - 2b = 3b + 11

3b -1

b times b times b = b3 b plus b plus b = 3b

2b - 1

Change the order to make it more obvious: 3a - a + 2b + 4b 2a + 6b or 2 (a + 3b).

The answer to 4a times 3b equals 1.3. You have to find the value of A and B.

(3b + 7x)(3b + 7x) or (3b + 7x)2

(a+b)(3b+1)

5 + 10ac + 3b

2a+3b+4c cannot be added. They are not like terms. Like terms need to have the same variable in order to be added.

It is a2 - 9b2.

3b

(2a + b)(a + 3b)

3a + (3b - 2a) + 5b =3a + 3b - 2a + 5b =(3a - 2a) + (3b + 5b) =a + 8b

8a+b+32a+3b=40a+4b

1a+3b 2a+4b=3a +7b